2018
DOI: 10.3390/su10041094
|View full text |Cite
|
Sign up to set email alerts
|

Internal Social Network, Absorptive Capacity and Innovation: Evidence from New Ventures in China

Abstract: This research investigates the impact of the internal social network on new venture's innovation by building a comprehensive structural equation modeling (SEM) that integrates three streams of research: internal social network, innovation, and absorptive capacity. Based on a sample of 279 new ventures from China, the current study's results show that absorptive capacity plays a full mediating effect in the relationship of the internal social network and innovation. Particularly, among the skill set of absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 122 publications
(164 reference statements)
0
32
0
Order By: Relevance
“…Mere skill and technology acquisition do not enhance a new venture's innovation. The effect of openness, such as social network, plays a greater role in the innovation process [53,54]. Linking social performance to economic performance reinforces performance by social enterprises.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mere skill and technology acquisition do not enhance a new venture's innovation. The effect of openness, such as social network, plays a greater role in the innovation process [53,54]. Linking social performance to economic performance reinforces performance by social enterprises.…”
Section: Discussionmentioning
confidence: 99%
“…The third includes organizational factors such as organizational structure, governance structure, organizational culture, leadership, cohesion, and organizational strategy [32,50,52]. Finally, performance is also driven by environmental factors such as network with stakeholders, social support, and government nonfinancial support [53,54]. The performance drivers of social enterprises are also related to each other.…”
Section: Relationship Between Social Entrepreneurs and Performance Ofmentioning
confidence: 99%
“…Absorptive capacity act as a moderator between the internal social network and innovation [46]. Empirical studies have used the total aggregate level of R&D expenditure as a proxy for innovation due to various reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that social capital has a significant effect on job searches and mobility [6][7][8], incomes [9], development, and innovation [10]. The roles of social capital in disaster recovery have also been highlighted.…”
Section: Introductionmentioning
confidence: 99%